Air Pollution and Migration: Exploiting a Natural Experiment from the Czech Republic - Stepan Mikula; Mariola Pytlikova (Institute of Labor Economics (IZA), 2021)
This paper examines the causal effects of air pollution on migration by exploiting a natural experiment in which desulfurization technologies were rapidly implemented in coal-burning power plants in the Czech Republic in the 1990s. These technologies substantially decreased air pollution levels without per se affecting economic activity. The results based on a difference-in-differences estimator imply that improvements in air quality reduced emigration from previously heavily polluted municipalities by 24%. We find that the effect of air pollution on emigration tended to be larger in municipalities with weaker social capital and fewer man-made amenities. Thus, our results imply that strengthening social capital and investing in better facilities and public services could partially mitigate depopulation responses to air pollution. Finally, we look at heterogeneous migratory responses to air pollution by education and age and find some evidence that the more educated tend to be more sensitive to air pollution in their settlement behavior.
Keywords: Q53; J61; O15; 330; natural experiment; migration; air pollution